Dampak Reputasi, Responsifitas, Pemberian Hadiah, dan Rekomendasi terhadap Nasabah yang Berpindah dari BSI ke Bank Konvensional - Asakdiyah, Salamatun; Rachmiani; Musafir; Hasim (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims to investigate the impact of reputation, responsiveness, gift-giving, and recommendations on Brand Switching, especially the movement of customers from Conventional Banks to Bank Syariah Indonesia (BSI). The research method uses multiple linear regression with a Likert Scale to collect data from 100 respondents who are customers from various cities in Indonesia, including Yogyakarta, Gorontalo, and Surakarta. The validity test results show that all variables have a valid correlation with Brand Switching. Multiple linear regression revealed that gifts had the greatest impact, while recommendations had a lower impact. The F test and t-test confirm that reputation, responsiveness, gift-giving, and recommendations simultaneously and partially significantly influence Brand Switching. Even though the Multiple R shows a relationship of 61.7%, the Adjusted R Square of 35.5% indicates that the model does not fully explain variations in Brand Switching. The conclusions of this research provide insight for bank management to improve reputation, responsiveness, and gift-giving strategies to reduce the level of Brand Switching. Future research is recommended to consider additional variables and a qualitative approach to explore the factors that influence customer decisions.